Analysis of the Causes of Turbine Power Efficiency Decreases: Analisis Penyebab Efisiensi Daya Turbin Menurun - Kurniawan, Ricky; Akbar, Ali (Procedia of Engineering and Life Science, 2024)
Abstract. The steam turbine as the prime mover converts steam energy into kinetic energy and kinetic energy is further converted into mechanical energy in the form of rotation of the shaft turbine. Turbines as generator drives so as to produce electric power that can be used in various industrial fields. The energy required is large and the continuous use of the turbine must operate with sufficient stability for a long time. Turbine efficiency will decrease due to several factors such as errors during operation and duration of maintenance. Based on data obtained from PT. Synergy of Gula Nusantara PG. Kremboong turbine power efficiency will decrease because there are several factors that cause corrosion, erosion and wear and tear on turbine engine components. Steam for turbine drive produced by steam boilers containing dirt or inappropriate water ph can cause scale on the turbine so that the turbine cannot rotate optimally.